The reaction of the armed forces to hybrid threats - the Greek case - Tsailas, Demetrios (Array, 2020)
We know that the strategy must create the basic knowledge that links both the ways and the means to achieve the desired political goals and strategic results. This logical method is a continuous thought process that provides strategic intent and informs ways, creating links to strategic planning that lead to the use of means, in military operations. This factor is the element that includes calculating, sleight and creating a logic or chain of results in strategy. In this paper, after considering a strategy distillation, we will analyze the context of hybrid warfare in strategic planning, which is of particular concern to us in Greek-Turkish relations.